Application of the Combination of SMART and TOPSIS Methods in the Decision Support System for the Selection of KIP-K Recipients in Students of the Islamic University of Balitar - Alwan Fauzaan; Haris Yuana; Udkhiati Mawaddah (LPPM Telkom University Surabaya, 2025)
This research aims to develop a decision support system that combines the Simple Multi-Attribute Rating Technique (SMART) method and the Technique for Order of Preference by Similarity to the Ideal Solution (TOPSIS) in the selection process for recipients of the Indonesia Smart Lecture Card (KIP-K) at the Islamic University of Balitar. The KIP-K program is an initiative of the Indonesian government to provide financial assistance to students with economic limitations but high academic potential, aiming to increase access to higher education for the underprivileged. However, in the implementation at the Islamic University of Balitar, there was an obstacle when several students who should have met the requirements and were entitled to receive the KIP-Lecture did not get it. The process without a structured calculation method and the calculation of data that is carried out individually are the main problems. This study collected and analyzed data on prospective KIP-K recipients with a decision support system developed. The research stages include data collection, normalization of criterion weights using the SMART method, and calculating priority scores using the TOPSIS method. The results of this system are measured using confusion matrix to evaluate the recommendation's accuracy. Using a confusion matrix shows that the resulting recommendation system has an accuracy rate of around 94.92%, precision of around 93.75%, recall of around 93.75%, and F1-score of 93.75, which is included in the excellent classification. This proves that combining methods can provide results based on the selection needs of KIP-K recipients at the Islamic University of Balitar.